2 ABSENCE OF MAJOR CARDIOVASCULAR EVENT IN A GROUP OF PATIENTS FOLLOWED FOR MORE THAN ONE YEAR AFTER SEVERE COVID-19 PNEUMONIAE. (15th December 2022) - Salvotti, Francesca; Tosoni, Federico; Borghi, Erika; Fusco, Elena Maria; Volpe, Pietro; Zanotti, Eros; Scipione, Vittorio; Flamminio, Gigliola; Pastori, Antonella; Pedroni, Leonardo; Napoli, Federico; Santagiuliana, Marzia; et al.
Abstract: Introduction: The Coronavirus disease 2019 (COVID-19), doesn't affect only respiratory system, but it also involves other organs including cardiovascular system, possibly causing acute or chronic cardiovascular events. Preexisting cardiovascular diseases enhance COVID-19 morbidity, as well. Aim: In this retrospective analysis we investigated the onset of cardiovascular events during a time-span of more than one year since hospitalization (384 days). Methods: The analysis included 43 patients, who were hospitalized in Internal Medicine Department of Montichiari Hospital (ASST Spedali Civili of Brescia) for moderate to severe SARS-CoV2 related pneumonia treated with high-flow oxygen support (ranging from 40% fraction of inspired oxygen to non-invasive ventilation) Mean age was 63 years, 28% (12/43) were female and 72% (31/43) were male. Thirty-five percent of the patients suffered from heart diseases, 56% of them were hypertensives and 23% had type 2 diabetes; 12% had chronic kidney disease (CKD) and 5% an active neoplasm. 49% of the sample was obese. Nineteen percent took ACE inhibitors and 19% was on ARBs. Statins were taken by 37% of the patients; an antiaggregant by 21%, and an anticoagulant by 2% (see table) Results: The follow-up visit included the evaluation of post-covid infection quality-of-life, standard laboratory tests, chest computed tomography, spirometry with evaluation of DLCO. The onset of cardiovascular events during the average period of 384 days was evaluated. None of the 43 patients had major cardiovascular events: coronary heart disease, cerebrovascular disease, peripheral arterial disease, deep vein thrombosis and pulmonary embolism. Conclusions: Even if this study failed to demonstrate new-onset CV events, longer follow-up studies performed to evaluate cardiovascular risk following SARS-CoV1 infection showed persistent hyperlipidemia, cardiovascular system abnormalities, and glucose metabolism disorders in a very high number of patients. Further analyses are needed to further investigate longer term cardiovascular consequences of SARS-CoV2 infection.